2017
DOI: 10.3390/ma10101206
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Modification of Alloying Method on Inclusion Evolution in RH Refining of Silicon Steel

Abstract: This study explores the effect of introducing additional alloy elements not only in a different order but also at different stages of the Ruhrstahl-Heraeus (RH) process of low-carbon silicon steel production. A more economical method, described as “pre-alloying”, has been introduced. The evolution of MnO-FeO inclusions produced by pre-alloying was investigated. Results show that spherical 3FeO·MnO inclusions form first, then shelled FeO·zMnO (z = 0.7–4) inclusions nucleate on the surface of pre-existing 3FeO·M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Figure 9 shows the morphology of the SSD and SSW compacts before and after carbonation for 24 h (D-C24 and W-C24) and the carbonated compacts after seawater curing for 28 days (D-W28 and W-W28). The chemical composition of particles with typical morphology were tested by EDS spectra to assist with analysing their mineralogy [ 44 , 45 , 46 ]. As shown in Figure 9 a,b, the particles in both SSD and SSW became aggregated and/or agglomerated after mixing and moulding.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9 shows the morphology of the SSD and SSW compacts before and after carbonation for 24 h (D-C24 and W-C24) and the carbonated compacts after seawater curing for 28 days (D-W28 and W-W28). The chemical composition of particles with typical morphology were tested by EDS spectra to assist with analysing their mineralogy [ 44 , 45 , 46 ]. As shown in Figure 9 a,b, the particles in both SSD and SSW became aggregated and/or agglomerated after mixing and moulding.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information on the FeO-MnO inclusion formation after MCFeMn additions during the RH refining was reported by Li et al [88] They showed that spherical 3FeOAEMnO inclusions that were formed before the melt reached the solidification temperature could later act as heterogeneous nucleation sites for FeOAEzMnO shelled inclusions. Figure 16 represents the different Fe/Mn ratios in the core and shell of the inclusions, which have different solidification temperatures, and their evolution mechanism.…”
Section: Femn Alloysmentioning
confidence: 95%
“…Fig. 16-Fe/Mn ratio in the core and shell of FeO-MnO inclusions (a) and schematic illustration of the evolution of FeO-MnO inclusions (b).Reprinted from Ref [88],. under the terms of the Creative Commons CC BY license.…”
mentioning
confidence: 99%
“…They all believed that there are big differences between one steel and another, for their types of the inclusions and the effects of these inclusions on any one property of the two steels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Hence, even if some of these scholars maintained that inclusions could affect the magnetic properties of some silicon steel, but they did not concerned exclusively with inclusions and did not identify one concrete grade of silicon steel [11][12][13][14][15]. However, each grade of non-oriented silicon steel has its own types of inclusions, thus the mechanism by which inclusions affect the magnetic properties of different grades of silicon steel would not be the same.…”
Section: Introductionmentioning
confidence: 99%